Ellis van Creveld syndrome: An unusual presentation at birth - Singh, Vidisha; Agrawal, Alka; Aggarwal, Kailash Chandra (Indian Journal of Case Reports, 2021)
Ellis Van Creveld, a syndrome comprising of chondrodysplasia, bilateral polydactyly of the hands with skeletal abnormalities, and congenital heart defect is a rare autosomal recessive disease. The prevalence of the disease in the world is 1/6000–20,000 newborns. In the Indian population, it is difficult to estimate the exact prevalence of the disease but, it is mostly seen in the Amish population. The cardinal features are short stature, dysplastic nails and teeth, polydactyly, narrow chest, and heart defects. The crucial differentials are Jeune dystrophy, Weyers syndrome, and McKusick-Kaufman syndrome. Here, we report a neonate, born of a non-consanguineous marriage with a syndromic appearance consisting of a bell-shaped chest, polydactyly, natal teeth, and single atrium. Prognosis is related to respiratory and heart defects in the early neonatal period.